Ethical aspects of gender assignment in ambiguous genitalia - congenital adrenal hyperplasia: a case report - Nur Rochmah; Muhammad Faizi; Adwina Nurlita Kusuma Wardhani (Indonesian Pediatric Society, 2021)
Congenital adrenal hyperplasia (CAH) is an autosomal recessive disorder commonly caused by mutation of the CYP21A2 gene, resulting in deficiency of an enzyme required for cortisol synthesis in the adrenal cortex. In 90-95% of cases, the deficient enzyme is 21-hydroxylase (21-OH), with an incidence ranging from 1 in 5,000 to 15,000 live births across various ethnic and racial backgrounds. In classical 21-OH deficiency (21-OHD) CAH, excessive androgen exposure in the fetus results in virilization at birth.1 The management of ambiguous genitalia in children with CAH presents a unique and ethically challenging decision-making dilemma for the medical team. Insensitive and poorly informed statements made in the delivery room may cause long-term psychological problems for the families. It is important to refrain from assigning gender until sufficient diagnostic information can be gathered. Parents, as guardians, and the supporting medical team must make decisions on behalf of the child, with the goal of enabling the child to grow into a healthy and happy adult with his or her assigned gender.2,3 We report a case of a child with CAH, focusing on the ethical challenges in management of ambiguous genitalia.